2013
DOI: 10.1016/j.cellsig.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced production of TNF-α and IL-6 in mast cells is dependent on p38 but independent of TTP

Abstract: The production of the proinflammatory cytokines TNF-α and IL-6 is regulated by various mRNA-binding proteins, influencing stability and translation of the respective transcripts. Research in macrophages has shown the importance of the p38-MK2-tristetraprolin (TTP) axis for regulation of TNF-α mRNA stability and translation. In the current study we examined a possible involvement of p38 and TTP in LPS-induced cytokine production in bone marrow-derived mast cells (BMMCs). Using pharmacological inhibitors we init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…However, we found that the Itk −/− Btk −/− mast cells response to LPS is impaired activation of ERK and JNK, and enhanced p38 activation, suggesting that the function of ITK and BTK in mast cells might be pathway specific. This p38 activation pattern is consistent with the very recent findings that p38 critically regulates LPS-induced TNF-α production in BMMCs, while ERK activation is dispensable 40 . In Itk −/− Btk −/− mast cells, p38 may function to promote TNF-α protein translation, as its downstream effector MNK1 is an essential component in the hyper-production of TNF-α in LPS-stimulated mast cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, we found that the Itk −/− Btk −/− mast cells response to LPS is impaired activation of ERK and JNK, and enhanced p38 activation, suggesting that the function of ITK and BTK in mast cells might be pathway specific. This p38 activation pattern is consistent with the very recent findings that p38 critically regulates LPS-induced TNF-α production in BMMCs, while ERK activation is dispensable 40 . In Itk −/− Btk −/− mast cells, p38 may function to promote TNF-α protein translation, as its downstream effector MNK1 is an essential component in the hyper-production of TNF-α in LPS-stimulated mast cells.…”
Section: Discussionsupporting
confidence: 91%
“…The MAPK p38 also exhibited enhanced basal phosphorylation, and was further significantly induced by stimulation of LPS in Itk −/− Btk −/− BMMCs. In contrast, activation of ERK and JNK was impaired (Figure 6, 3 rd to 8 th panels) 40 . Thus, ITK and BTK differentially regulate MAPKs in mast cell response to LPS, with regulatory role in p38 signaling activation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It's major role in the regulation of corneal epithelial proliferation and differentiation in corneal mice cell culture has been reported 59 . This protein has been shown to be also involved in the regulation of the production of cytokines 60 and, the gamma proteoform, is up-regulated during LPS-induced cardiomyocytes injury 61 . Its major role in Toll-like receptors activation has also been demonstrated and its involvement in the lipopolysaccharide-induced production of tumor necrosis factor by macrophages has been documented 62 .…”
Section: Molecular Biosystems Accepted Manuscriptmentioning
confidence: 99%
“…In a double-blind human study, a 5-wk supplementation with n-3 PUFAs significantly decreased exhaled NO from young (22-29-yr-old) asthma patients challenged with low-dose dust mite allergen, reduced the blood eosinophil count and inhibited the antigeninduced cysLT production by isolated leukocytes from these patients [153]. These results indicate that the effect of n-3 PUFAs on allergic responses might be dependent on how n-3 PUFAs are provided to the patients in terms of the PUFA dose, the Inhibition [69] IL-5 Human, mouse [70,71] Stimulates eosinophil differentiation and function [72] Inhibition [69] IL-6 Human, mouse [61,73] Induces B cell and cytotoxic T cell differentiation, promotes macrophage activation [74] Unknown IL-8 Human, mouse [57,75] Recruits monocytes/macrophages, promotes angiogenesis [76] Unknown IL-10 Human, mouse [71,77] Inhibits macrophage activation, promotes regulatory T cell function [78] Unknown IL-13 Human, mouse [71,79] Promotes eosinophil recruitment and airway smooth muscle cell contractility [80,81] Inhibition [69] IL-17 Human [82] Promotes tissue remodeling and production of proinflammatory cytokines [83] Unknown IL-33 Mouse [84] Promotes regulatory T cell function and Th2 response [85] Unknown (continued on next page) specific type of n-3 PUFAs, the age of the subjects, and the severity of their disease.…”
Section: N-3 Pufasmentioning
confidence: 84%